Challenging zircon coatings by suspension plasma spraying. Issue 10 (August 2022) - Cañas, E.; Rosado, E.; Alcázar, C.; Orts, M.J.; Moreno, R.; Sánchez, E.
Abstract: Zircon is a ceramic material that decomposes at high temperature, limiting its use by conventional thermal spraying. In this work, it is intended to use thermal spraying from concentrated aqueous suspensions to evaluate the possibility of obtaining coatings in which a significant proportion of zircon could be preserved. For this purpose, stable concentrated suspensions of zircon have been prepared, which have been subsequently sprayed at two different spraying distances. The coatings were characterised in terms of microstructural features and the amount of zircon present in the coatings was quantified. All the coatings obtained display the typical microstructure derived from the deposition of liquid feedstocks by plasma spraying. In all cases, the XRD analysis demonstrates the partial decomposition of zircon into zirconia and residual silica, but also that a significant percentage (about 20%) is preserved without decomposing, which marks a strong difference with respect to reported data for atmospheric plasma spraying.